Observation of anti-dark solitons in fiber lasers - Zhao, L. M. (2018)
We report on the numerical simulation and experimental observation of anti-dark solitons in fiber lasers. The anti-dark solitons were obtained in the net normal near zero dispersion regions where the third-order dispersion plays a role. .